Faktor-faktor Risiko Kelainan Kadar Hemoglobin pada Pengendara Ojek Motor Online di Kawasan Industri Tanjung Mas Kota Semarang - Lilik Setyowatiningsih; Ririh Jatmi Wikandari (Poltekkes Kemenkes Semarang, 2023)
Air pollution can affect health conditions, CO and Pb are one of the compositions of vehicle exhaust gases that are dangerous. Online motorcycle taxi drivers have a high risk of exposure to pollutants. This research aims to determine the risk factors that affect hemoglobin levels in online motorcycle taxi drivers in the Tanjung Emas Area of Semarang City. The method used observational analytics with a cross-sectional approach. The total population in this study was 55 respondents and the number of respondents was determined using total sampling. Based on the results of examining hemoglobin levels using a hematology analyzer, of 55 respondents, 47 respondents had normal hemoglobin levels and 8 respondents had abnormal hemoglobin levels. The results of the Chi square test on smoking status have a significant relationship (p=0.04) to the blood hemoglobin level of online motorcycle taxis in the Tanjung Emas Area of Semarang city while in the status of Education, length of work, and knowledge there is no significant relationship (0.05) to the hemoglobin level of online motorcycle taxi drivers in the Tanjung Emas Area of Semarang City. The conclusion of this study is that there is a significant relationship between smoking status and hemoglobin levels of online motorcycle taxi drivers in the Tanjung Emas Area of Semarang City and there is no significant relationship between education factors, length of work time, and knowledge of hemoglobin levels of online motorcycle taxis in the Tanjung Emas Area of Semarang City.